Perspective and modeling requirement on household solid waste management - Aswan Munang; Hari Purnomo; Winda Nur Cahyo; Imam Djati Widodo (Mechanical Engineering for Society and Industry, 2026)
Rapid economic and population growth, urbanization, and resource overexploitation have intensified household solid waste generation, creating serious environmental challenges, particularly in developing countries. Despite various efforts, waste management systems remain inadequate, hindered by poor infrastructure, limited recycling practices, and insufficient disposal facilities. However, existing models often overlook the behavioral dimension of waste generation. This study aims to identify and assess critical factors influencing the development of effective household waste management by integrating food practices into the Theory of Planned Behavior (TPB), thereby addressing a significant theoretical gap. A systematic literature review of 78 peer-reviewed articles published between 2014 and 2024 was conducted to extract key influencing factors and conceptual models. The created model concept will be evaluated using the Analytical Hierarchy Process (AHP) based on expert judgment to determine the relative importance of each variable. Five experts were selected using purposive sampling from four stakeholder entities: academia, government, industry, and community. The analysis revealed 11 interrelated factors, with pro-environmental behavior (23.8%), government policy (18.7%), and public attitude (14.8%) emerging as the most influential. The findings highlight that behavioral change, supported by robust policy frameworks, is essential for enhancing household-level waste management. This study offers a comprehensive decision-support model that integrates behavioral, institutional, and technological interventions, providing actionable insights for policymakers and practitioners in promoting sustainable consumption and waste reduction practices.